Linseed oil supplementation alters milk fatty acid profile, mitigates heat stress, and improves summer milk yield in grazing dairy cows - Gheno G.C.* (2024)
© The Author(s), under exclusive licence to Springer Nature B.V. 2024.Dietary supplementation of fat can be an important source of energy to compensate for the reduction in dry matter intake in dairy cows during heat stress periods. Studies have reported that supplementing dairy cow diets with linseed oil (LO) can increase milk yield and enhance the levels of beneficial fatty acids, such as omega-3 fatty acids, in the milk. The objective of this research was to evaluate the effect of LO supplementation on milk fatty acids profile, milk yield and composition, and physiological parameters of grazing cows. The study was conducted in two seasons, one in spring and one in summer. A 2 × 2 Latin square design was used in each experiment. Twelve Holstein and crossbred Holstein x Jersey cows were involved in each season. Cows were divided into two groups: control (TC) with no supplementation and treatment (TL) supplemented with 400 g/day of LO. The results showed that LO supplementation altered the milk fatty acid profile: decreased concentrations of short and medium-chain fatty acids (C10:0 - C17:1) except for C13:0 and increased concentrations of long-chain fatty acids (C18, C18:1 (both trans and cis isomers), C18:2 (specific conjugated linoleic acid - CLA isomers), and C18:3 n3 (omega-3)). Additionally, milk yield increased by 1.5 l per day during summer in LO-supplemented cows, while milk fat, protein, and casein content decreased. Milk stability increased by 2.2% in the LO-supplemented group. LO-supplemented cows reduced internal body temperature and heart frequency in the afternoon and increased daily rumination time by 20 min. In conclusion, LO supplementation can be an effective strategy to improve the nutritional profile of milk by altering fatty acid composition towards potentially healthier fats, mitigate the negative effects of heat stress on grazing cows during summer, as evidenced by reduced body temperature and heart frequency and increase milk yield.